Non‐Linear Effects of Soda Taxes on Consumption and Weight Outcomes. (10th March 2014) - Fletcher, Jason M.; Frisvold, David E.; Tefft, Nathan
Abstract The potential health impacts of imposing large taxes on soda to improve population health have been of interest for over a decade. As estimates of the effects of existing soda taxes with low rates suggest little health improvements, recent proposals suggest that large taxes may be effective in reducing weight because of non‐linear consumption responses or threshold effects. This paper tests this hypothesis in two ways. First, we estimate non‐linear effects of taxes using the range of current rates. Second, we leverage the sudden, relatively large soda tax increase in two states during the early 1990s combined with new synthetic control methods useful for comparative case studies. Our findings suggest virtually no evidence of non‐linear or threshold effects. Copyright © 2014 John Wiley & Sons, Ltd.